Barriers to accessing physical rehabilitation after stroke: an integrative review (Research, Society and Development, 2022)
Stroke is one of the main public health problems in the world. It represents the second leading cause of death, and is currently considered the most disabling disease in the world. More than half of the affected patients need rehabilitation, which aims to minimize the sequelae and restore some degree of functional independence, raising their quality of life and reducing the burden generated by the disease. The objective of this review was to know the access to these services offered by the health systems. The search was conducted in the following databases: PubMed, SCOPUS, SciELO, Chocrane, and LILACs. The terms were: "Access to physiotherapy", "stroke", "rehabilitation", and their respective terms in Portuguese present in Medical Subject Headings (MeSH) and in DeCS (Descriptors in Health Sciences). The search included articles published in the last 10 years, in Portuguese, English and Spanish. Of the 353 articles found, 21 met the inclusion criteria for data analysis based on PRISMA guidelines. It was observed in this review that although the approaches and the importance of physical rehabilitation in stroke patients are already well discussed, the access is still difficult, with several barriers such as: insufficient staff, lack of structure, bureaucracy, difficulty in moving around, and lack of understanding about the services. However, the current system of care organization can be improved, using new concepts of structure and care process, creating a more effective communication between the health system, patients and caregivers.